Evaluation of confirmatory data following the Article 12 MRL review for dimethenamid‐P. (10th April 2019) - ,; Anastassiadou, Maria; Brancato, Alba; Carrasco Cabrera, Luis; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; Pedersen, Ragnor; et al.
Abstract: The applicant BASF SE submitted a request to the competent national authority in Germany to evaluate the confirmatory data that were identified for dimethenamid‐P in the framework of the maximum residue level (MRL) review under Article 12 of Regulation (EC) No 396/2005 as not available. The data gap refers to the submission of a plant metabolism study investigating the fate of dimethenamid‐P following foliar treatment with a short preharvest interval (PHI) in a leafy or bulb vegetable crop. The confirmatory data requirement is considered sufficiently addressed according to the conclusions of the peer review, which, based on available metabolism studies, proposed to modify the existing enforcement and risk assessment residue definitions in all plant commodities, by including additional dimethenamid‐P metabolites ((2 RS )‐3‐(2‐(2, 4‐dimethylthiophen‐3‐yl)[(2 S )‐1‐methoxypropan‐2‐yl]amino‐2‐oxoethanesulfinyl)‐2‐hydroxypropanoic acid (M30) and (2 RS )‐3‐[(2‐(2, 4‐dimethylthiophen‐3‐yl)[(2 S )‐1‐methoxypropan‐2‐yl]amino‐2‐oxoethyl)sulfanyl]‐2‐hydroxypropanoic acid (M26). The residue data of metabolites M26 and M30 are currently not available for all authorised uses assessed in the MRL review. Should risk managers decide amending residue definitions, the existing EU MRLs would need to be revised accordingly. The consumer exposure as calculated by the MRL review was updated in two scenarios, using the existing and the new toxicological reference values as derived by the peer review. For the crops under consideration (spring onions, lettuce, escarole and herbs), indicative conversion factors were applied to account for possible metabolite burden. No consumer intake concerns were identified.